Online score‐informed source separation in polyphonic mixtures using instrument spectral patterns. Issue 4 (21st May 2019) - Muñoz‐Montoro, A. J.; Vera‐Candeas, P.; Cortina, R.; Combarro, E. F.; Alonso‐Jordá, P.
Abstract : Soundprism is a real‐time algorithm to separate polyphonic music audio into source signals, given the musical score of the audio in advance. This paper presents a framework for a Soundprism implementation. A study of the sound quality of the online score‐informed source separation is shown, although a real‐time implementation is not carried out. The system is compound of two stages: (1) a score follower that matches a MIDI score position to each time frame of the musical performance; and (2) a source separator based on a nonnegative matrix factorization approach guided by the score. Real audio mixtures composed of an instrumental quartets were employed to obtain preliminary results of the proposed system.